The IMS graduate review 1990 - Pearson, Richard [Verfasser]; Pike, Geoffrey [Verfasser] (My University, 1990)
"The purpose of this annual IMS Review is to provide employers and others with the latest information on the state of supply and demand in the graduate labour market. This information is essential if employers are to develop effective policies and practices to minimise their recruitment and employment problems in the future. The format of this year's Review is rather different from in previous years. The emphasis this year is on presenting the key trends and issues graphically together with a short commentary for each figure. Together the figures cover the full range of base data relating to entry to higher education, the output, subsequent destinations and the future supply and demand for graduates. Some of this information represents an updating of earlier editions (2,3) and related publications (4); new subjects include ethnic origins of students; the early careers of graduates; and European Schemes to aid student mobility within the Community. The Review starts, however, with an overview of the key trends and issues affecting the graduate labour as we go into the 1990s." (author's abstract) Der Report stellt aktuelle Informationen zum Angebot und Bedarf an hochqualifizierten Arbeitskräften in Grossbritannien zusammen. Die Basisdaten vermitteln ein Bild von den Haupttrends in der Beschäftigung von Hochschulabsolventen in den 90er Jahren. (IAB)
Hochschulabsolventen-Bericht 1990 des IMS (Institute of Manpower Studies)
Keywords: P 2.1.5 Fachhochschul- und Hochschulreife; G 1.3.2.2.3 Zweite Schwelle, in Arbeit; G 1.3.3 Bildungs- & Erwerbsbiografien; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; S 5 Organisationsentwicklung; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; Hochschule; Absolvent; Berufseinmündung; Berufsverlauf; Arbeitskräfteangebot; Arbeitskräftenachfrage; Berufswahl; Beschäftigtenstruktur; Arbeitslosigkeit; Einkommen; Quantitative Angaben